Definition of "positional isomer" as it pertains to the control of schedule I controlled substances. Final rule (Federal register, 2007)
On May 25, 2006, DEA published a Notice of Proposed Rulemaking which proposed the addition of a specific definition for the term "positional isomer" to allow for the systematic determination of which isomers of schedule I substances would be considered to be "positional," and therefore, subject to schedule I control. This rulemaking finalizes that definition. The Controlled Substances Act (CSA) and its implementing regulations specify which hallucinogenic substances are considered schedule I controlled substances. The CSA states that all salts, isomers, and salts of isomers of these substances are also schedule I controlled substances. In non-technical terms, an isomer of a substance is a different compound, but a compound which has the same number and kind of atoms. The terms "optical isomer" and "geometric isomer" are specific scientific terms and it is easy to determine whether one substance is an optical or geometric isomer of another. The term "positional isomer," however, is subject to scientific interpretation. The addition of a definition for the term "positional isomer" will assist legitimate research[ers] and industry in determining the control status of materials that are "positional isomers" of schedule I hallucinogens. While the DEA will remain the authority for ultimately determining the control status of a given material, providing a specific definition for "positional isomer" will ensure consistent criteria are utilized in making these determinations. This rule does not change existing laws, regulations, policies, processes, and procedures regarding the determination of control status for schedule I hallucinogenic substances. This rule merely makes available to the public the longstanding definition of "positional isomer" which DEA has used when making these scheduling determinations. This rule is relevant only to specialized forensic or research chemists. Most of these individuals are existing DEA registrants who are authorized by the DEA to handle schedule I hallucinogenic substances.